2014
DOI: 10.1080/14616742.2014.952126
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Harms and their Interface with International Criminal Law

Abstract: G e n d e r e d H a r m s a n d t h e i r I n t e r f a c e w i t h I n t e r n a t i o n a l C r i m i n a l L a w NORMS, CHALLENGES AND DOMESTICATION † FIONNUALA NÍ AOLÁ INMany feminists have questioned the extent to which the law can ever effectively deter violence against women given the ways in which the law and criminal justice systems often act to reinforce deeply sexist assumptions about women, their sexual and social identities and their relation to the social (male) world. While acknowledging law's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sceptics are a broad church ranging from scholars of radical feminism and Third World Approaches to International Law (TWAIL) to ‘sex-positive’ scholars. Radical feminists are sceptical of criminal law’s potential to advance feminism by which they mean the liberation of women from patriarchy (Ní Aoláin, 2014; Snider, 1998). They argue that law continues to be steeped in patriarchal norms which efface gender inequality and often render women less visible.…”
Section: The Rome Statute Feminism and International Criminal Lawmentioning
confidence: 99%
“…Sceptics are a broad church ranging from scholars of radical feminism and Third World Approaches to International Law (TWAIL) to ‘sex-positive’ scholars. Radical feminists are sceptical of criminal law’s potential to advance feminism by which they mean the liberation of women from patriarchy (Ní Aoláin, 2014; Snider, 1998). They argue that law continues to be steeped in patriarchal norms which efface gender inequality and often render women less visible.…”
Section: The Rome Statute Feminism and International Criminal Lawmentioning
confidence: 99%
“…Regarding the presence of women in the judicial branch, the research mainly focuses on the analysis of the dimensions related to descriptive or substantive representation. On the one hand, some researches study how do international courts decide on cases about women's rights (Bensouda, 2014;Durbach and Chappell, 2014;Grey, 2014;Ní Aoláin, 2014). On the other hand, there are researches in which the use of gender-neutral language is analyzed as a topic for analysis in judicial decisions (Oosterverld, 2014;Koomen, 2014;Kenney, 2010;Maveety, 2010).…”
Section: Revista De Estudiosmentioning
confidence: 99%
“…Additionally, the study of the presence of women in high courts is interesting because unlike other arenas of political decision-making, the institutional mechanisms of positive or reverse discrimination are practically nonexistent (Bensouda, 2014;Durbach y Chappell, 2014;Grey, 2014;Ní Aoláin, 2014;Scribner y Lambert, 2010;Hoekstra, 2010). In fact, Htun and Piscopo (2014) have shown that while legislatures have made considerable progress in establishing quota laws, there are no proposals of this type in the judicial arena.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have hereby highlighted law's co-constitutive role in the social, economic, and political relations central to (mal)development, such that law 7 E. g. see, from very different perspectives, Charlesworth and Chinkin (2000), Conaghan (2014), Davies (2013), Engle Merry (2006), Musembi (2013), Manji (2010). 8 On trafficking see especially Bernstein (2012) and Kotisworan (2014); on violence see especially Ni Aoláin (2014) and Tapia Tapia (2018); on rape and international criminal law see Buss (2011), Halley (2008), Nikolic-Ristanovic (2005). 9 E. g. Engle (2005), Engle Merry (2006), Musembi (2013).…”
Section: Introduction: Bumping Into Legal Furniturementioning
confidence: 99%
“…Another of my hopes is that legally-curious feminist development critics can move past what Fionnuala Ni Aoláin, in her account of the growing attention to international criminal law within campaigns to end Violence against Women, calls the "lost in translation" critique (Aoláin 2014). In this, rather than theorise or critically analyse the demand for more law within GAD, development scholars and/or practitioners end up noting the implementation gap between law and practice, and trying to reduce it, with 'law plus' measures that leave law itself, and its role within uneven development and gender inequality, uninterrogated.…”
Section: Introduction: Bumping Into Legal Furniturementioning
confidence: 99%